Bombs and Babies: Exposure to Terrorism and Fertility Choices in Nigeria. (27th December 2021) - Rotondi, Valentina; Rocca, Michele
Abstract: The aim of terrorism all over the world is to have fear rule over people's lives. The consequences of terrorist attacks, however, are substantially different across contexts. In this paper we study the association between exposure to Boko Haram's attacks and households' fertility choices in Nigeria. We hypothesise that households exposed to terrorism increase their number of children as a way to insure against future unexpected shocks. We test this hypothesis using geolocalised panel data linked to information on terrorist attacks that occurred in the region. Consistent with our hypothesis, terrorism is found to increase fertility (proxied by the number of surviving children per household): a one standard deviation increase in the number of fatalities increases the probability that a household hit by terrorism has a newborn by $1%$ . This association is robust to the use of difference-in-differences and instrumental variables models—and therefore can be given a causal interpretation.